1989
DOI: 10.1212/wnl.39.4.561
|View full text |Cite
|
Sign up to set email alerts
|

End‐plate dysfunction in acute organophosphate intoxication

Abstract: Acute organophosphate intoxication resulting from suicide attempts in 14 patients produced a series of electrophysiologic abnormalities that correlated with the clinical course. Spontaneous repetitive firing of single evoked compound muscle action potentials (CMAP) was the earliest and most sensitive indicator of the acetylcholinesterase inhibition. A decrement of evoked CMAP following repetitive nerve stimulation was the most severe abnormality. At the height of the intoxication no CMAP was evoked after the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 1 publication
1
43
0
4
Order By: Relevance
“…At RBC-AChE activity of about 15 % to 20 % mainly decrement-increment-phenomena occurred (23). This type of response is typically found in moderate to severe poisoning (37,38), presumably also indicating the need for artificial ventilation. At RBC-AChE activity above 30 %, little disturbance of neuromuscular transmission could be detected (23).…”
Section: Investigation Of Neuromuscular Transmissionmentioning
confidence: 90%
See 1 more Smart Citation
“…At RBC-AChE activity of about 15 % to 20 % mainly decrement-increment-phenomena occurred (23). This type of response is typically found in moderate to severe poisoning (37,38), presumably also indicating the need for artificial ventilation. At RBC-AChE activity above 30 %, little disturbance of neuromuscular transmission could be detected (23).…”
Section: Investigation Of Neuromuscular Transmissionmentioning
confidence: 90%
“…A series of experiments on phrenic nerve-diaphragmpreparations of mice circumfused with paraoxon showed that obidoxime restored muscle force, and this was clearly accompanied by an increase in muscle AChE activity (36). Comparably, in patients with insecticide OP-poisoning, it was reported that low RBC-AChE activity (<10 %) was associated with marked decrement-phenomena (23) (stimulation of a nerve with frequencies of 30 Hz to 50 Hz and recording of compound action potentials), indicating severe disturbance of neuromuscular transmission and urgent requirement of artificial ventilation (37,38). At RBC-AChE activity of about 15 % to 20 % mainly decrement-increment-phenomena occurred (23).…”
Section: Investigation Of Neuromuscular Transmissionmentioning
confidence: 96%
“…In acute organophosphate poisoning, nerve conduction velocities and distal latencies are normal, even in severely paralyzed patients [104]. The earliest and most sensitive indicator of the AChE inhibition is a small amplitude of compound muscle action potential after single supramaximal stimulation with often repetitive activity [104,105]. On repetitive nerve stimulation, there is usually no decrement when stimulating at 3 Hz, and only occasional decrement at 10 Hz.…”
Section: Nerve Agentsmentioning
confidence: 99%
“…On repetitive nerve stimulation, there is usually no decrement when stimulating at 3 Hz, and only occasional decrement at 10 Hz. At 30 or 50 Hz, there may be a decrement-increment response [104] in less severe stages of poisoning [105].…”
Section: Nerve Agentsmentioning
confidence: 99%
“…21,22 This and the other neurotoxic syndromes associated with organophosphorus poisoning have since then been electrophysiologically characterized. 3,23,24 Accepted for publication January 12, 2000. Reprints …”
Section: Mechanism Of Actionmentioning
confidence: 99%